Green light-emitting material of beta-diketone Schiff base terbium zinc complex and preparation method of green light-emitting material

By using green light luminescent materials with β-dione Schiff base terbium zinc complex, the shortcomings of existing materials in terms of mechanical properties, thermal stability, chemical resistance and light sensitivity are solved, and the efficient and solid color green light luminescent effect is achieved, and the preparation process is simplified.

CN119775324APending Publication Date: 2025-04-08TAIZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510034013.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing green light luminescent materials have shortcomings in mechanical properties, thermal stability, chemical resistance and light sensitivity, and the production method is complex and needs improvement.

Method used

The β-dione Schiff base terbium zinc complex was used as the green light luminescent material, and the β-dione Schiff base terbium zinc complex with good mechanical properties, thermal stability, chemical resistance and high sensitivity luminescent material was prepared through steps 1 to 4 in the synthesis route.

Benefits of technology

It realizes efficient luminescence of green light luminescent materials, with pure chromaticity, high quantum yield and long fluorescence lifetime. At the same time, the preparation method is simplified, with simple operation, mild reaction conditions and high product purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775324A_ABST
    Figure CN119775324A_ABST
Patent Text Reader

Abstract

The invention discloses a green light-emitting material of a beta-diketone Schiff base terbium zinc complex and a preparation method of the green light-emitting material, and belongs to the technical field of light-emitting materials, the molecular formula of the beta-diketone Schiff base terbium zinc complex is C61H53ClN2O9TbZn, the preparation method of the green light emitting material comprises the steps of synthesis of a Schiff base ligand, synthesis of a Schiff base zinc complex, synthesis of a Schiff base terbium zinc complex and synthesis of a beta-diketone Schiff base terbium zinc complex. The maximum ultraviolet absorption wavelength and the maximum fluorescence emission wavelength in acetonitrile are 360 nm and 546 nm respectively, the compound can serve as a stable green light emitting material, and the preparation method is easy to operate, mild in reaction condition, high in product purity, good in green light emitting effect, suitable for large-scale production and convenient for practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of luminescent materials, and in particular to a green light luminescent material of a beta-diketone Schiff base terbium zinc complex, a preparation method and an application thereof. Technical Background

[0002] The development history of rare earth luminescent materials can be traced back to the 1960s. With the breakthrough of rare earth separation technology, high-purity single rare earth oxides were prepared, and the excellent properties of rare earth elements in luminescence were developed and utilized.

[0003] Lanthanide metals have unique optical properties and long fluorescence lifetimes, but the ff transition of lanthanide metal ions is forbidden, resulting in low luminescence efficiency. In the prior art, red phosphors doped with lanthanide metals and other substances are generally prepared.

[0004] The Chinese invention patent with application number 202010668321.4 and application date of July 13, 2020 discloses a europium-terbium-doped lanthanum molybdate composite carbon nitride phosphor and a preparation method thereof. The prepared europium-terbium-doped lanthanum molybdate composite carbon nitride phosphor has good crystallinity, uniform particle size, can be effectively excited by near-ultraviolet light, and has high luminescence intensity; the europium-terbium-doped lanthanum molybdate composite carbon nitride phosphor obtained by the invention can be spectrally controlled within a wide range of red light-green light, red light-blue light, and green light-blue light, and bright white light emission can be obtained, which solves the problems existing in the luminescence intensity and ratio control of the three-primary color phosphor; the method has abundant raw material sources, low cost, simple synthesis process, easy operation, good repeatability, and can be prepared in large quantities.

[0005] The Chinese invention patent application numbered 201610907464.X, filed on October 19, 2016, discloses a cerium-terbium co-doped borate phosphor and a preparation method thereof. 3+ -Tb 3+ The energy transfer system obtains a fluorescent powder that can be tuned from blue light to green light emission under near-ultraviolet excitation, has high external quantum efficiency and excellent thermal stability, and as a high-efficiency blue-green fluorescent powder, has the potential to be applied to ultraviolet / near-ultraviolet LED chip-based white light LEDs. The present invention also provides a method for preparing the above fluorescent powder, which has a simple preparation process, is pollution-free, and is easy to operate.

[0006] The invention patent with application date of May 14, 2009 and application number 200910098779.4 discloses a method for preparing terbium-doped yttrium oxide green light luminescent powder, wherein yttrium nitrate and terbium nitrate of different molar ratios are dissolved in deionized water, sodium hydroxide solution is added, and after being fully stirred, the mixture is placed in a hydrothermal kettle with a filling degree of 80-90%, and the mixture is kept warm at a temperature range of 150-250°C for 8-24 hours. Finally, the prepared powder sample is centrifuged and dried, and then heat-treated at 400-800°C for 2-4 hours under nitrogen protection to obtain a terbium-doped yttrium oxide green light luminescent powder material. The invention adopts a hydrothermal synthesis process to prepare a terbium-doped yttrium oxide powder material that emits green light, and the molecular formula is Y2O3:Tb 3+ The product is a flaky powder with a strong green light emission peak at 544.5 nanometers, which belongs to Tb 3+ of 5 D 4 → 7 F 5 At the same time, the nitrogen protection during heat treatment prevents Tb 3+ The effect of oxidation greatly improves the luminescence efficiency of the product.

[0007] However, in the above-mentioned prior art, the mechanical properties, thermal stability, chemical resistance and photosensitivity of the green light luminescent materials produced therein need to be further improved, and the production method also needs to be further improved. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a green light emitting material of a β-diketo Schiff base terbium zinc complex, which has good mechanical properties, thermal stability, chemical resistance and high sensitivity. At the same time, the present invention provides a preparation method of the green light emitting material of the β-diketo Schiff base terbium zinc complex, which has simple operation, mild reaction conditions and high product purity.

[0009] The present invention provides a green light emitting material of a β-diketone Schiff base terbium zinc complex, wherein the structural formula of the β-diketone Schiff base terbium zinc complex is: The molecular formula of β-diketone Schiff base terbium zinc complex is: 61 H 53 C1N 2 O 9 TbZn, molecular weight: 1215.20.

[0010] The present invention provides a preparation method of a green light luminescent material of a β-diketone Schiff base terbium zinc complex, the preparation method comprising the following steps: Step 1, Synthesis of Schiff base ligand: (1S, 2S)-1,2-diphenylethylenediamine and o-vanillin are reacted to prepare Schiff base ligand H 2 L, whose structural formula is: Step 2, Synthesis of Schiff base zinc complex: 2 L and anhydrous zinc acetate Zn(CH 3 COO 3 The reaction synthesizes Schiff base zinc complex ZnL, whose structural formula is: Step 3, synthesis of terbium zinc complex: Schiff base zinc complex ZnL and TbCl 3 6H 2 O reflux reaction, obtain Schiff base terbium zinc complex, the structural formula of which is: Step 4, synthesis of β-diketo Schiff base terbium zinc complex: add dibenzoylmethane to the Schiff base terbium zinc complex in step 3, react at room temperature, let stand, filter, and volatilize to obtain orange-yellow crystals, solution β-ZnTbL, β-ZnTbL is (1S, 2S)-1,2-diphenylethylenediamine o-vanillin β-diketo terbium zinc complex, that is, β-diketo Schiff base terbium zinc complex, and its structural formula is:

[0011] As a further improvement measure of the present invention, the preparation method of the green light emitting material of the above-mentioned β-diketo Schiff base terbium zinc complex is as follows: in step 1, anhydrous methanol is added, and the molar ratio of (1S, 2S)-1,2-diphenylethylenediamine and o-vanillin is 1:2, and refluxed for 6 hours by magnetic stirring, then cooled, filtered under reduced pressure, washed with methanol 2 to 3 times, and dried in a drying oven to obtain the Schiff base ligand H 2 L, the Schiff base ligand H obtained in this way 2 L is a light yellow solid with high yield.

[0012] As a further improvement measure of the present invention, the preparation method of the green light emitting material of the above-mentioned β-diketone Schiff base terbium zinc complex comprises: in step 2, the Schiff base ligand H 2 L and Zn(CH 3 COO 3 The molar ratio was 1:1, the reaction temperature was set at 25°C, the reflux reaction time was 10 hours, and then the mixture was filtered under reduced pressure.

[0013] As a further improvement measure of the present invention, the preparation method of the green light emitting material of the above-mentioned β-diketone Schiff base terbium zinc complex, the Schiff base zinc complex and TbCl 3 6H 2 The molar ratio of O was 2:1, the reaction temperature was set at 25 °C, and the reflux reaction time was 10 h.

[0014] As a further improvement measure of the present invention, in the preparation method of the green light emitting material of the above-mentioned β-diketo Schiff base terbium zinc complex, the molar ratio of the terbium zinc complex to dibenzoylmethane in step 4 is 1:2.

[0015] As a further improvement measure of the present invention, in the preparation method of the above-mentioned green light emitting material of the β-diketo Schiff base terbium zinc complex, the reaction time of the dibenzoylmethane and terbium zinc complex solution in step 4 is set to 9 to 11 hours.

[0016] As a further improvement measure of the present invention, in the preparation method of the above-mentioned green light luminescent material of the β-diketo Schiff base terbium zinc complex, the reaction time of the dibenzoylmethane and terbium zinc complex solution in step 4 is set to 10 hours, so that the reaction is more complete and the product yield is high.

[0017] As a further improvement measure of the present invention, a preparation method of the green light emitting material of the above-mentioned β-diketo Schiff base terbium zinc complex is provided, and the green light emitting material of the β-diketo Schiff base terbium zinc complex is used in an organic optoelectronic display.

[0018] The beneficial effects of the present invention are as follows: 1. The present invention provides a green light luminescent material of a β-diketo Schiff base terbium zinc complex, wherein the maximum ultraviolet absorption and fluorescence emission wavelengths in acetonitrile are 360 ​​nm and 546 nm respectively, the green light luminescence effect is good, the chromaticity of the luminescence is pure, the quantum yield of β-ZnTbL is high, and the fluorescence lifetime is long; 2. The green light luminescent material of a Schiff base β-diketo Schiff base terbium zinc complex provided by the present invention can be used as a green light material in the field of electronic luminescence, and the material can emit green light and can be used as a luminescent material in the field of optoelectronic materials; 3. The preparation method adopted by the material of the present invention is simple to operate, the reaction conditions are mild, and the product purity is high. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the solid fluorescence excitation emission diagram of β-ZnTbL of the present invention.

[0020] Figure 2 This is the UV-visible absorption diagram of β-ZnTbL of the present invention.

[0021] Figure 3 This is the fluorescence lifetime decay diagram of β-ZnTbL of the present invention.

[0022] Figure 4 It is the infrared spectrum of β-ZnTbL of the present invention. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0024] A green light emitting material of a β-diketone Schiff base terbium zinc complex, the structural formula of which is: The molecular formula is: C 61 H 53 C1N 2 O 9 TbZn, molecular weight: 1215.20.

[0025] By doping terbium rare earth complexes into LEDs, the luminous intensity of the green light portion can be significantly improved, thereby achieving efficient white light LEDs.

[0026] Example 1, a preparation method of a green light luminescent material of a β-diketone Schiff base terbium zinc complex, take (1S, 2S)-1, 2-diphenylethylenediamine (2.1200g, 10mmol) and o-vanillin (3.3500g, 22mmol), put them in a 50ml round-bottom flask, add 25ml of anhydrous methanol, stir magnetically at a speed of 500r / min, reflux for 6 hours, and then cool in a refrigerator until a large amount of light yellow solid precipitates, and filter under reduced pressure. Wash with methanol 2 to 3 times, dry in a drying oven, and obtain Schiff base ligand H 2 L, Schiff base ligand H 2 L is a yellow powder, weighing 4.0810 g, with a yield of 84.99%. Its synthesis route is as follows:

[0027] Take the dried Schiff base ligand (1.0130g, 2.1mmol) and place it in a 25ml round-bottom flask, add 20ml methanol to dissolve it, and then add anhydrous zinc acetate (0.4366mg, 2.31mmol). Reflux the reaction at room temperature for 10 hours, and filter to obtain a light green solid product Schiff base zinc complex ZnL 0.6756mg, with a yield of 59.34%. Its synthesis route is as follows:

[0028] Take the dried Schiff base zinc complex (0.545 g, 1 mmol) and place it in a 25 ml round bottom flask, add 10 ml methanol to dissolve it, and then add TbCl 3 6H2 O (0.219 g, 0.11 mmol). Reflux reaction at room temperature for 10 hours to obtain 0.456 g of terbium zinc complex solution with a reaction yield of 67.65%. The synthesis route is as follows:

[0029] Dibenzoylmethane (0.450g, 2mmol) was added to the terbium zinc complex solution and refluxed at room temperature for 10 hours. After standing and filtering, the filtrate was encapsulated in a 15mL long test tube and allowed to stand and evaporate. After one week, orange-yellow crystals β-ZnTbL were precipitated, 0.674g, and the reaction yield was 55.56%. β-ZnTbL is (1S, 2S)-1,2-diphenylethylenediamine condensed o-vanillin β-diketone terbium zinc complex, that is, β-diketone Schiff base terbium zinc complex. A small amount of methanol was used to wash away the Schiff base zinc complex attached to the surface of the crystal, and after filtering, it was placed in a fume hood to dry naturally. Its synthesis route is as follows:

[0030] The β-ZnTbL complex has an excitation wavelength of 395 nm and emission wavelengths of 496, 547, 585, and 620 nm, respectively. 5 D 4 → 7 F 6 , 5 D 4 → 7 F 5 , 5 D 4 → 7 F 4 , 5 D 4 → 7 F 2 , the quantum yield is 1.16%, and the fluorescence lifetime is 4431ns.

[0031] The present invention utilizes the strong light absorption ability of organic aromatic ligands to transfer energy to lanthanide metal atoms through the antenna effect, so that the lanthanide metal is transformed from the ground state to the excited state, and the excited state of the lanthanide metal radiates strong light through transitions at different energy levels. The present invention uses Schiff base zinc complex as a sensitizer for lanthanide metal luminescence in fluorescent materials, and the lanthanide metal selects terbium (Tb) element that can emit unique green light. This element can be used to produce green light luminescent materials, so the application in luminescent materials has important research value and broad application prospects.

[0032] Terbium rare earth complexes have excellent luminescence properties and chemical stability. In the field of LEDs, terbium rare earth complexes are widely used to improve the luminescence efficiency and thermal stability of LED lamps. In addition, terbium complexes are also used to synthesize rare earth organic complexes with high luminescence efficiency and thermal stability. These materials have important application prospects in the design of optoelectronic devices. In the field of magnetism, multinuclear terbium complexes based on Schiff base ligands show unique magnetic properties, such as slow magnetic relaxation behavior and magnetic cooling properties, which make them potential in the development of magnetic refrigeration materials. In biomedical applications, terbium complexes are used as fluorescent probes and bioimaging materials for biological activity detection and gene expression visualization. These complexes enhance their biological activity by binding to specific organic ligands, and have low toxicity, which provides a basis for the development of new, efficient and low-toxic rare earth drugs. In the field of catalysts and energy materials, terbium rare earth complexes can act as catalysts for petroleum cracking, alkylation and hydrogenation reactions. In addition, terbium complexes can also be used to prepare high-performance lubricant additives, which can improve the extreme pressure performance and anti-wear performance of lubricants and extend their service life. These applications not only improve the efficiency of industrial production, but also reduce environmental pollution.

[0033] Example 2, a preparation method of a green light luminescent material of a β-diketo Schiff base terbium zinc complex, take (1S, 2S)-1, 2-diphenylethylenediamine (1.2581g, 6mmol) and o-vanillin (1.9896, 12mmol), put them in a 50ml round-bottom flask, add 25ml of anhydrous methanol, stir magnetically at a speed of 500r / min, reflux for 10 hours, and then cool in a refrigerator until a large amount of light yellow solid precipitates, and filter under reduced pressure. Wash with methanol 2 to 3 times, dry in a drying oven, and obtain Schiff base ligand H 2 L, Schiff base ligand H 2 L is a yellow powder, weighing 1.0766 g, with a yield of 37.36%.

[0034] Take the dried Schiff base ligand (1.0404 g, 2.16 mmol) and place it in a 25 ml round bottom flask, add 20 ml methanol to dissolve it, and then add anhydrous zinc acetate (0.4549 g, 2.5 mmol). Reflux the reaction at room temperature for 10 hours, and filter to obtain 0.647 g of a light green solid product, Schiff base zinc complex ZnL, with a yield of 55.25%.

[0035] Take the dried Schiff base zinc complex (0.556 g, 1 mmol) and place it in a 25 ml round-bottom flask. Add 10 ml of methanol to dissolve it. Then add TbCl 3 6H 2O (0.221 g, 0.5 mmol). The reaction was refluxed at room temperature for 10 hours to obtain 0.3348 g of terbium zinc complex solution with a reaction yield of 49.67%.

[0036] Dibenzoylmethane (0.447 g, 2 mmol) was added to the terbium zinc complex solution and refluxed at room temperature for 10 hours. After standing and filtering, the filtrate was packaged into a 15 mL long test tube and allowed to stand and evaporate. After one week, orange-yellow crystals were precipitated to obtain a yellow-green transparent solution of β-ZnTbL, 0.324 g, and a reaction yield of 26.70%. After filtering, the solution was placed in a fume hood and dried naturally.

[0037] Example 3, a preparation method of a green light luminescent material of a β-diketo Schiff base terbium zinc complex, take (1S, 2S)-1, 2-diphenylethylenediamine (2.0473g, 10mmol) and o-vanillin (3.36329g, 22mmol), put them in a 50ml round-bottom flask, add 25ml of anhydrous methanol, stir magnetically at a speed of 500r / min, reflux for 10 hours, and then cool in a refrigerator until a large amount of light yellow solid precipitates, and filter under reduced pressure. Wash with methanol 2 to 3 times, dry in a drying oven, and obtain Schiff base ligand H 2 L, Schiff base ligand H 2 L is a yellow powder, weighing 3.265 g, with a yield of 68.00%.

[0038] Take the dried Schiff base ligand (0.9623 g, 2 mmol) and place it in a 25 ml round bottom flask, add 20 ml methanol to dissolve it, and then add anhydrous zinc acetate (0.3636, 2 mmol). Reflux the reaction at room temperature for 10 hours, and filter to obtain 1.2542 g of a light green solid product, Schiff base zinc complex ZnL, with a yield of 68.07%.

[0039] Take the dried Schiff base zinc complex (0.537, 1 mmol) and place it in a 25 ml round bottom flask. Add 10 ml of methanol to dissolve it, and then add TbCl 3 6H 2 O (0.21 g, 0.05 mmol). The mixture was refluxed at room temperature for 10 hours to obtain 0.456 g of terbium zinc complex solution with a reaction yield of 67.65%.

[0040] Add dibenzoylmethane (0.450, 2mmol) to the terbium zinc complex solution and reflux for 10 hours at room temperature. Sit and filter, encapsulate the filtrate into a 15mL long test tube, and let it stand and evaporate. After one week, orange-yellow crystals precipitate to obtain a yellow-green transparent solution of β-ZnTbL 0.334g, with a reaction yield of 27.53%. After filtering, place it in a fume hood to dry naturally.

[0041] Embodiment 4, from Figure 1 As shown, 10 mg of luminescent material was weighed and dissolved in acetonitrile to prepare 2.0×10 -4 Mol / L solution, pipette 3.0 ml of the above solution into a cuvette, and then measure it on a TZS 980 steady-state fluorescence / phosphorescence chromatograph, with the excitation slit and emission slit widths both being 3 nm, and the excitation wavelength being 395 nm. It can be seen that the maximum fluorescence emission wavelength is 546 nm.

[0042] Example 5, the ultraviolet absorption spectrum was measured on a UV-2401PC Shimadzu ultraviolet spectrophotometer. The test was carried out at room temperature and ambient atmospheric pressure. The normalized results of the absorption test spectrum are shown in Figure 2 As can be seen from the figure, the maximum ultraviolet absorption wavelength is 360nm.

[0043] Example 6, the fluorescence lifetime data was measured on a TZS 980 steady-state fluorescence / phosphorescence spectrometer.

[0044] The fitting formula used is:

[0045] Where R(t) is the fluorescence intensity at time t; B i is the pre-exponential factor of the i-th exponential component; τ i is the lifetime of the i-th exponential component; R(0) is the initial fluorescence intensity of the sample,

[0046] Substituting each parameter into the formula, we can get the fluorescence lifetime: 12078ns, such as Figure 3 .

[0047] Example 7: 10 mg of luminescent material was weighed and mixed with KBr, crushed, pressed into tablets, and tested with an infrared spectrometer (IS10).

[0048] like Figure 4 As shown, IR (KBr, cm -1):3385.76,3058.34,2839.73,2360.41,1628.16,1594.50,1549.17,1518.01,1476.98,1453.11,1439.01,1385.69,1295.74,1239.10,1220.55,1169.16,110 0.65,1074.77,1023.89,978.74,941.64,850.97,813.57,783.69,741.82,722.57,700.97,641.24,627.25,617.92,607.63,545.77,523.66,454.26,426.46.

[0049] Example 8: The quantum yield was determined using an integrating sphere method on a TZS 980 steady-state fluorescence / phosphorescence spectrometer.

[0050] The quantum yield was directly measured to be 1.16%.

[0051] The specific formula is as follows:

[0052] where Φ F is the quantum yield of the sample; E b is the fluorescence integral of the sample (the number of emitted photons); A is the absorbance value at the excitation wavelength; I S is the excitation peak area of ​​the sample; I R It is the excitation peak area of ​​the blank sample, and the data is automatically calculated by the test instrument.

[0053] The above describes the implementation mode of the present invention in detail in conjunction with the accompanying drawings, but the specific embodiments described are only illustrative of the present invention. The present invention is not limited to the above implementation modes. For ordinary technicians in this field, several modifications and improvements can be made without departing from the present invention, which should also be regarded as belonging to the protection scope of the present invention.

Claims

1. A green light emitting material of a β-diketone Schiff base terbium zinc complex, characterized in that: The structural formula of the β-diketone Schiff base terbium zinc complex is:

2. The preparation method of the green light emitting material of the β-diketone Schiff base terbium zinc complex according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1, synthesis of Schiff base ligand: preparing Schiff base ligand H2L by condensation reaction of (1S, 2S)-1,2-diphenylethylenediamine and o-vanillin; Step 2, synthesis of Schiff base zinc complex: reacting Schiff base ligand H2L with anhydrous zinc acetate Zn(CH3COO)3 to synthesize Schiff base zinc complex ZnL; Step 3, synthesis of Schiff base terbium zinc complex: reflux the Schiff base zinc complex ZnL and TbCl3·6H2O to obtain the Schiff base terbium zinc complex; Step 4, synthesis of β-diketo Schiff base terbium zinc complex: add dibenzoylmethane to the Schiff base terbium zinc complex solution in step 3, react at room temperature, let stand and filter to obtain a yellow-green transparent solution β-ZnTbL, i.e. β-diketo Schiff base terbium zinc complex.

3. The preparation method of the green light emitting material of the β-diketone Schiff base terbium zinc complex according to claim 2, characterized in that: In step 1, anhydrous methanol is added, and the molar ratio of the (1S, 2S)-1,2-diphenylethylenediamine to o-vanillin is 1:

2. The mixture is refluxed for 6 hours with magnetic stirring, cooled, and filtered under reduced pressure.

4. The method for preparing a green light emitting material of a β-diketone Schiff base terbium zinc complex according to claim 2, characterized in that: The molar ratio of the Schiff base ligand H2L and Zn(CH3COO)3 described in step 2 is 1:1, the reaction temperature is set at 25°C, the reflux reaction time is 10 hours, and then the reduced pressure is filtered.

5. The method for preparing a green light emitting material of a β-diketone Schiff base terbium zinc complex according to claim 2, characterized in that: The molar ratio of the Schiff base terbium zinc complex and TbCl3·6H2O described in step 3 is 2:1, the reaction temperature is set at 25°C, and the reflux reaction time is 10 hours.

6. The method for preparing a green light emitting material of a β-diketone Schiff base terbium zinc complex according to claim 2, characterized in that: The molar ratio of the terbium zinc complex and dibenzoylmethane described in step 4 is 1:

2.

7. The method for preparing a green light emitting material of a β-diketone Schiff base terbium zinc complex according to claim 6, characterized in that: The reaction time of the dibenzoylmethane and terbium zinc complex solution in step 4 is set to 9 to 11 hours.

8. The method for preparing a green light emitting material of a β-diketone Schiff base terbium zinc complex according to claim 7, characterized in that: The reaction time of the dibenzoylmethane and terbium zinc complex solution in step 4 is set to 10 hours.

9. The use of a green light emitting material of a β-diketone Schiff base terbium zinc complex according to claim 1, characterized in that: The green light emitting material of the beta-diketone Schiff base terbium zinc complex is used in an organic photoelectric display.

Citation Information

Patent Citations

  • Method for preparing terbium-doped yttria green-light luminescent powder

    CN101560389B

  • Borate phosphor codoped with cerium and terbium and preparing method thereof

    CN106544021A

  • Europium-terbium-doped lanthanum molybdate composite carbon nitride phosphor and its preparation method

    CN111778024B